2018
DOI: 10.1016/j.plabm.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Should sex differences be considered when applying mathematical indices and formulas for discriminating β- thalassemia minor from iron deficiency?

Abstract: Backgroundβ-thalassemia minor (BTM) and iron deficiency (ID) are common disorders characterized by microcytosis and/or hypochromasia, leading to a challenge in their discrimination during mass-screening programs especially in developing countries where resources are limited. It has been shown with varying reliability that quick exclusion of either disorder could be achieved mathematically using RBC-based indices and formulas. However, none of these proposed indices and formulas considered the sex-based hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Matos et al, [6] reported that its sensitivity was 99.3%, Specificity 76.7% and YI was 76.0%, and the evaluation of this index by Arora et al, [22] showed high sensitivity to detect IDA (98.81%), excellent diagnostic accuracy and showing good applicability as screening tool in clinical practice. On the other hand Sirdah et al, [5] [25]. The present study found the MCI and RDWI indices to be best at differentiating IDA from β-TT.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Matos et al, [6] reported that its sensitivity was 99.3%, Specificity 76.7% and YI was 76.0%, and the evaluation of this index by Arora et al, [22] showed high sensitivity to detect IDA (98.81%), excellent diagnostic accuracy and showing good applicability as screening tool in clinical practice. On the other hand Sirdah et al, [5] [25]. The present study found the MCI and RDWI indices to be best at differentiating IDA from β-TT.…”
Section: Discussionsupporting
confidence: 43%
“…Many attempts are done in the last decades to simplify the differential diagnosis between IDA and β-TT, and as a result, several indices using blood cell count parameters are made but none of these indices or formulas provided an absolute discrimination power. The index or formula that offered the highest discrimination power for one population, yet, it showed moderate or low power when applied to other populations [5]. Application of these indices depends on racial Open Journal of Blood Diseases [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, blood count parameters, such as RBC, significantly differed between the females and males of each group. This finding is consistent with the study by Mahmoud, 22 which highlighted the importance of gender differences in the development and application of mathematical DFs. Therefore, to improve the diagnostic efficiency of TT, it is reasonable to stratify the cohort into male and female subcohorts before developing DFs that are unique to each group (Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…This could also be a possible explanation of variable results obtained in different studies. In our study equal numbers of male and female patients were taken to exclude this difference [24].…”
Section: Discussionmentioning
confidence: 99%